2016
DOI: 10.1111/all.12888
|View full text |Cite
|
Sign up to set email alerts
|

Endotypes of pollen‐food syndrome in children with seasonal allergic rhinoconjunctivitis: a molecular classification

Abstract: In a Mediterranean country characterized by multiple pollen exposures, PFS is a complex and frequent complication of childhood SAR, with five distinct endotypes marked by peculiar profiles of IgE sensitization to panallergens. Prospective studies in cohorts of patients with PFS are now required to test whether this novel classification may be useful for diagnostic and therapeutic purposes in the clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
5
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 35 publications
4
62
5
9
Order By: Relevance
“…The significant association between asthma and PFAS has also been reported in previous studies. [7][8][9] Our data, showed no differences in age, gender, duration of the pollen-related primary allergic disease, between the patients with and without PFAS. Contrary to this result, two previous studies reported longer durations of allergic rhinitis in patients with PFAS.…”
Section: Risk Factors Of Pfasmentioning
confidence: 42%
See 2 more Smart Citations
“…The significant association between asthma and PFAS has also been reported in previous studies. [7][8][9] Our data, showed no differences in age, gender, duration of the pollen-related primary allergic disease, between the patients with and without PFAS. Contrary to this result, two previous studies reported longer durations of allergic rhinitis in patients with PFAS.…”
Section: Risk Factors Of Pfasmentioning
confidence: 42%
“…In the recent multicenter study of Mastrorilli et al, which is performed in Italy, in another Mediterranean country, kiwi fruit was also the food that is most commonly triggering PFAS. 8 Another large study performed in Italy, also reported kiwi fruit to be the most frequently reported plant-derived food to be a cause of allergic reactions. 12 Allergic reactions to kiwi have been reported in association with birch and grass pollen allergies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Multiple sensitizations were common: 14 were monosensitized, 37 were sensitized to 2–3 allergens and 49 % to more than 3 allergens. This point out that molecular diagnosis would be often necessary to distinguish between polysensitized children who are sensitized to genuine allergens and those sensitized to cross-reactive allergens [11]. The average number of symptoms in the atopic group was 3.3 vs 2.8 in the non-atopic group.…”
Section: Reviewmentioning
confidence: 99%
“…Whether Gal1 can alleviate oral allergy has not been investigated. Since some foods can be the offending antigens of oral allergy [10], we hypothesize that oral allergy and intestinal allergy may concomitantly occur, a phenomenon may be designated the “oral-intestinal allergy syndrome (OIAS)”. To test this, we sensitized mice by application of antigens to the mouse buccal mucosa.…”
Section: Introductionmentioning
confidence: 99%